Homo temporalis : German Jewish thinkers on time - Lebovic, Nitzan, 1970- (Ithaca, New York : Cornell University Press and Cornell University Library, 2024)
"A group of modern Jewish intellectuals grappled with concepts of time and temporality. Martin Buber, Walter Benjamin, Hannah Arendt, and Paul Celan stand at the center of our contemporary understanding of religion, critical theory, politics, and literature. All four rejected notions of borders, territory, or national origin. Their path teaches us about three 'temporal turns'-in 1900, in 1945, and in 2000."--
A temporal turn -- Martin Buber: a time for theopolitics -- Walter Benjamin: the rhythm of time -- Against self-referentiality: Hannah Arendt reads Augustine -- Paul Celan: the syntax of time -- Life-form: after the turn.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 15, 2025).
JSTOR
Keywords: Buber, Martin, -- 1878-1965.; Benjamin, Walter, -- 1892-1940.; Arendt, Hannah, -- 1906-1975.; Celan, Paul; Time -- Religious aspects -- Judaism; Time -- Philosophy -- History -- 20th century; Time in literature; Jewish philosophy -- Germany -- 20th century; Temps -- Philosophie -- Histoire -- 20e siècle.; Temps dans la littérature.; Philosophie juive -- Allemagne -- 20e siècle.; POLITICAL SCIENCE / History & Theory; Electronic books